Transnasal endoscopic medial maxillary sinus wall transposition with preservation of structures. (21st December 2015) - Maxfield, Alice Z.; Chen, Tiffany T.; Scopel, Tiago F.; Engle, Robert; Piastro, Kristina; Butrymowicz, Anna; Kenning, Tyler; Pinheiro‐Neto, Carlos D.
Abstract : Objectives/Hypothesis: To evaluate the increase in access to the maxillary sinus (MS) with transnasal endoscopic medial maxillary sinus wall transposition (TEMMT), while preserving major structures of the nasal cavity. Study Design: The study was divided into three parts: anatomical, radiographic, and case series. Methods: Three cadaveric dissections (total of six sides) confirmed the feasibility of the TEMMT approach. Radiographic measurements using maxillofacial computed tomography scans were taken to assess the maximal antrostomy. The TEMMT approach was performed on six consecutive patients with benign MS disease. Results: The cadaveric measurements were consistent with the radiographic measurements, which confirmed the maximum access to the MS. The radiographic measurements ranged from 14.4 to 39.1 mm in the anteroposterior dimension, 8.2 to 23.7 mm in the superior‐inferior dimension, and 36° to 98° in the angle between the medial and anterior wall of the MS. In the patient series, five patients presented with an odontogenic cyst, and one patient had an antrochoanal polyp in the MS. The TEMMT approach provided excellent access and adequate resection, as well as preservation of the nasolacrimal duct and inferior turbinate. Finally, the mucosal flap was sufficient to cover the inferior meatal antrostomy. Conclusions: TEMMT provides excellent access into the MS, especially the floor and anterior wall, without the morbidities of the Caldwell‐Luc or medial maxillectomy approach. In addition, the transposition of the inferior turbinate and the mucosal flap provides coverage of the medial wall with preservation of the inferior meatus, inferior turbinate, and nasolacrimal duct for patients with benign MS disease. Level of Evidence: NA Laryngoscope, 126:1504–1509, 2016